A Stand-Off Laser-Induced Breakdown Spectroscopy (LIBS) System Applicable for Martian Rocks Studies - Changqing Liu; Zongcheng Ling; Jiang Zhang; Zhongchen Wu; Hongchun Bai; Yiheng Liu (Remote Sensing, 2021)
Laser-induced breakdown spectroscopy (LIBS) is a valuable tool for evaluating the geochemical characteristics of Martian rocks and was applied in the Tianwen-1 Mars exploration mission with the payload called Mars Surface Composition Detection Package (MarSCoDe). In this work, we developed a laboratory standoff LIBS system combined with a Martian simulation chamber to examine the geochemical characteristics of igneous rocks, with the intention to provide a reference and a basis for the analysis of LIBS data acquired by MarSCoDe. Fifteen igneous geological standards are selected for a preliminary LIBS spectroscopic study. Three multivariate analysis methods were applied to characterize the geochemical features of igneous standards. First, quantitative analysis was done with Partial Least Squares (PLS) and Least Absolute Shrinkage and Selection (LASSO), where the major element compositions of these samples (SiO2, Al2O3, T Fe2O3, MgO, CaO, K2O, Na2O, and TiO2) were derived. The predicted concentrations ((Fe2O3 + MgO)/SiO2, Fe2O3/MgO, Al2O3/SiO2, and (Na2O + K2O)/Al2O3) were used to identify the geochemical characteristics of igneous rocks. Also, PCA, an unsupervised multivariate method was tested to directly identify the igneous rock lithology with no prior quantification. Higher correlation (0.82–0.88) are obtained using Principal Component Analysis (PCA) scores than using predicted elemental ratios derived by PLS and LASSO, indicating that PCA is better suited to identify igneous rock lithology than via quantitative concentrations. This preliminary study, using this LIBS system, provides suitable methods for the elemental prediction and geochemical identification of martian rocks, and we will use extended geologic standards and continue to build a robust LIBS spectral library for MarSCoDe based on this LIBS system in the future.